2013
DOI: 10.1111/ijlh.12103
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte cell population data (volume conductivity scatter) in postprandial leukocyte activation

Abstract: Postprandial leukocyte activation is accompanied by temporary changes in leukocyte cell population data, similar to changes observed during various infections, but to a lesser extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…As reported previously, an increase in CR1 expression by monocytes and neutrophils occurs upon the ingestion of a fat meal (35). On average, monocytes and neutrophils express 20,000 to 140,000 CR1 molecules per cell (36,37).…”
Section: Discussionsupporting
confidence: 70%
“…As reported previously, an increase in CR1 expression by monocytes and neutrophils occurs upon the ingestion of a fat meal (35). On average, monocytes and neutrophils express 20,000 to 140,000 CR1 molecules per cell (36,37).…”
Section: Discussionsupporting
confidence: 70%
“…In addition to identifying peripheral leukocyte subsets, automated hematology analyzers also generate data in identifiable patterns that correspond to numerous pathologic conditions. Algorithms that identify patients with bacterial infections , viral infections , malaria , asthma , myocardial infarction , postprandial leukocyte activation , and chronic lymphoproliferative disorders have been described on numerous commercially available hematology analyzers. These algorithms routinely generate data to predict whether patients have the condition in question.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies that investigated the effect of glucose on leukocytes' markers of activation have shown conflicting results in T2D [ 45 48 ]. On the other hand, postprandial studies reported that leukocytes are activated by lipids [ 38 , 49 , 50 ]. The expression of leukocytes' markers of activation (i.e., CD11b, CD11c) increased on monocytes or neutrophils after a high fat meal [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%